2017
DOI: 10.1016/j.envpol.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Fate and mass balance of bisphenol analogues in wastewater treatment plants in Xiamen City, China

Abstract: Due to the well-known endocrine disrupting ability of bisphenol A (BPA), its production and usage have been regulated. Consequently, other bisphenol analogues (BPs) have been used as the replacement of BPA. Despite their widespread use, few studies have investigated the occurrence and fate of BPs in wastewater treatment plants (WWTPs). In this study, we conducted a city-wide monitoring survey and collected the wastewater and sludge samples from seven WWTPs in Xiamen, China over seven days. The concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(69 citation statements)
references
References 42 publications
(55 reference statements)
5
61
3
Order By: Relevance
“…Although some BPA-like effects are hypothesized because of their similar chemical structures, BPS is presently unregulated and can be used without restriction, which has led to a sharp increase in its production and use [ 8 ]. Consequently, BPS has been detected in dust, water, sediment, sewage sludge and effluent samples [ 9 , 10 ], and in human urine and blood serum [ 11 ], at concentrations that are generally lower than BPA, but of the same order of magnitude [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some BPA-like effects are hypothesized because of their similar chemical structures, BPS is presently unregulated and can be used without restriction, which has led to a sharp increase in its production and use [ 8 ]. Consequently, BPS has been detected in dust, water, sediment, sewage sludge and effluent samples [ 9 , 10 ], and in human urine and blood serum [ 11 ], at concentrations that are generally lower than BPA, but of the same order of magnitude [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they suggested combining these catalytic processes with other treatment processes such as biological treatment, UV treatment, and ultrasound treatment processes to improve the removal of these target compounds from WW. Furthermore, Sun et al compared five different advanced treatment processes, namely, coagulation sedimentation, magnetic polyacrylic anion exchange resin adsorption, activated carbon adsorption, and ozonation and electro‐adsorption to prevent the effects of endocrine disruption in municipal wastewater secondary effluent. They reported that all of the advanced oxidation treatment options that they tested were efficient for the removal of endocrine disruption effects from WW.…”
Section: Introductionmentioning
confidence: 99%
“…Average removal efficiency of emerging contaminants from wastewater during different advanced treatment processes. Data taken from elsewhere …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations